Independent energy storage planning model considering comprehensive benefits enhancement - Wenzhang Guo; Yuanke Zhou; Rui Zhang; Han Su; Jia Tian; Xudong Hu; Yuming Shen; Jiayin Xu; Feiao Zhao; Yinghao Ma (AIP Advances)
New power systems with large-scale clean energy access require energy storage to provide critical support. Aiming at the problems of unclear service scope, high investment cost, long payback period, and low utilization rate faced by the construction of new energy storage, an energy storage planning method considering the comprehensive benefits of independent energy storage is proposed. First, the key transmission sections identification index is proposed by comprehensively considering the characteristics of the key transmission sections, the grid topology, the reliability, and the criticality of the line. Second, the connecting areas of the key transmission sections are selected as the location of independent energy storage configuration and dynamically updated year by year to clarify the optimal siting area of the independent energy storage in the long term planning. Then, an independent energy storage planning model considering comprehensive benefits enhancement is established to expand the multiple applications of energy storage in the power market and improve the comprehensive benefits of the energy storage system. Finally, the improved IEEE RTS-79 system is used for simulation to verify the effectiveness of the proposed method.